Digital Mind Mapping Using MindMeister on Writing: The Effect and Students’ Perceptions - Widya Ariyan Elsa (Retain: Journal of Research in English Language Teaching, 2025)
The purpose of this research is to explore the effect of applying digital mind mapping using MindMeister on students' writing performance in hortatory exposition texts and to examine students’ perceptions regarding its implementation in writing classes. An embedded mixed-method approach combine with a quasi-experimental design was employed involving 68 students from a public senior high school in Gresik Regency, Indonesia. Data were collected through writing tests and questionnaires. It was found that students in the experimental group significantly enhanced their writing performance (p = 0.000 < 0.05) in comparison to those in the control group. In addition, students demonstrated positive perceptions of digital mind mapping using MindMeister in terms of their attitude, activities, and overall writing experience. The findings indicate that digital mind mapping serves as a beneficial tool for enhancing students’ writing skills and engagement in the classroom.